The Sc2WxMo3−xO12 series as electrodes in alkali-ion batteries. Issue 21 (12th May 2021) - Liu, Junnan; Johannessen, Bernt; Brand, Helen E. A.; Andersen, Henrik L.; Sharma, Neeraj
Abstract : Herein, the series Sc2 W x Mo3− x O12 (0 ≤ x ≤ 3) is synthesised and the structure and electrochemical performance in alkali-ion batteries is characterised. Abstract : Herein, the series Sc2 W x Mo3− x O12 (0 ≤ x ≤ 3) is synthesised and the structure and electrochemical performance in alkali-ion batteries is characterised. The structures remain in the orthorhombic Pnca space group for the whole series with the lattice parameters increasing approximately linearly from { a = 9.6336(2) Å, b = 13.2406(3) Å, c = 9.5413(2) Å} in Sc2 Mo3 O12 to { a = 9.6735(2) Å, b = 13.3218(3) Å, c = 9.5811(2) Å} in Sc2 W3 O12 . Discharge against Li delivers a high initial discharge capacity of 1200 mA h g −1 for Sc2 Mo3 O12 with a reversible capacity of about 150 mA h g −1 after 100 cycles. Meanwhile the increase of W content reduces both the initial and overall capacities for all lithium, sodium and potassium half cells. The initial discharge capacity for Sc2 W3 O12 against lithium is only about 700 mA h g −1 with a reversible capacity of about 100 mA h g −1 after 100 cycles. For all sodium and potassium half cells across the series, the capacities drop dramatically after a few cycles and the reversible capacities are low, below 50 mA h g −1 . Structurally, the fully potassium discharged Sc2 Mo3 O12 partially transforms into a new P 4̄ space group KMo4 O6 phase, while the crystallinity decreases in both fully lithium and sodium discharged Sc2 Mo3 O12 . For Sc2 W3 O12, only fully potassium discharged Sc2 W3 O12 shows a decrease in crystallinity, while the fully lithium and sodium discharged Sc2 W3 O12 appears to become amorphous (or particles are too small to be examined with X-ray diffraction). X-ray absorption spectroscopy demonstrates that the Mo oxidation state changes with different type and amount of alkali-ion discharge. This work illustrates the influence of composition on the electrochemical performance in this family of compounds.